Self-isolation of adolescents after Covid-19 pandemic between social withdrawal and Hikikomori risk in Italy - Loredana Cerbara; Giulia Ciancimino; Gianni Corsetti; Antonio Tintori (Scientific Reports)
Abstract Social withdrawal is a widespread phenomenon among adolescents, presenting significant challenges in understanding its aetiology and dynamics. This study, drawing on data from two cross-sectional surveys conducted in 2019 and 2022 on students in public upper secondary schools, investigates the trend of self-isolation among Italian adolescents before and after the COVID-19 pandemic. The two nationally representative samples comprise 3273 and 4288 participants, respectively, with 46.3% and 41.2% identifying as female, ranging in age from 14 to 19 years. Using Multiple Correspondence Analysis (MCA) and Hierarchical Cluster Analysis (HCA), three distinct profiles of social withdrawal were identified among adolescents: “Social Butterflies”, “Friendship-Centric”, and “Lone Wolves”. Notably, the discovery of a subgroup within the Lone Wolves, composed of adolescents who never meet their friends and whose number has doubled post-pandemic, highlights the chronic nature of the phenomenon that demands urgent intervention. These findings shed light on the increase of self-isolation in Italy, showing the interplay of socio-demographic, psychological, and sociological factors underlying this phenomenon.